Proteins involved in actin filament organization are key host factors for Japanese encephalitis virus life-cycle in human neuronal cells. (December 2020) - Khasa, Renu; Sharma, Puja; Vaidya, Anuradha; Vrati, Sudhanshu; Kalia, Manjula
Abstract: Multiple membrane trafficking networks operate in the eukaryotic cell and are hijacked by viruses to establish infection. Recent studied have highlighted that viruses can exploit distinct pathways depending on the cell type. Japanese encephalitis virus (JEV), a neurotropic flavivirus, can infect neuronal cells through a clathrin-independent endocytic mechanism. To further characterize the membrane trafficking requirements for JEV infection of neuronal cells, we have performed a RNA interference-based study targeting 136 proteins in the human cell line IMR-32. Through quantitative RT-PCR and plaque assays we have validated that JEV infection in neuronal cells was independent of clathrin, and identified host-factors that were crucial for establishment of infection. Several of these proteins were involved in regulation of actin filament organization such as RHOA, RAC1, proteins of the ARP2/3 complex and N-WASP family, LIMK1, PAK1 and ROCK2. The small molecule inhibitors of ARP2/3 complex, CK-548 and of the N-WASP, Wiskostatin inhibited virus replication highlighting the important roles of these proteins in the virus life-cycle. We also identified ATG12, BECN1, VAPA, VAPB and VCP proteins as crucial host-factors for JEV replication across epithelial and neuronal cell lineages. Highlights: JEV can infect neuronal cells through clathrin-independent endocytosis. Actin filament organization proteins are crucial for JEV infection in neuronal cells. Small molecule inhibitors CK-548 and Wiskostatin inhibit JEV infection. Proteins ATG12, BECN1, VAPA, VAPB and VCP are host-factors for JEV replication.